2009
DOI: 10.1002/hyp.7484
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive approach to characterization of the nonlinearity of runoff in the headwaters of the Tarim River, western China

Abstract: Abstract:Nonlinear characteristics of the runoff processes in the headwaters of the Tarim River were identified and evaluated using several selected methods, including wavelet analysis, correlation dimension, and R/S analysis. Time-series of annual data describing runoff, average temperature, and precipitation from 1957 to 2005 were used to construct and test empirical models. The primary findings of this study were as follows: (1) The annual runoff of the headwaters are complex and nonlinear in nature, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Sun et al [42] found that pan evaporation in the Poyang Lake Basin increased from 2002, and it would attribute to the temperature increases. This was different from the snowmelt-dominated basins in China, such as Tarim River, western China [43] and Yarlung Zangbo River on the Tibetan Plateau [44], where elevated temperature produced higher stream flow because of enhanced snowmelt. However, as a whole, stream flow was more sensitive to precipitation than evaporation in the Poyang Lake Basin [45].…”
Section: Impacts Of Climate Change On Stream Flow Variationsmentioning
confidence: 66%
“…Sun et al [42] found that pan evaporation in the Poyang Lake Basin increased from 2002, and it would attribute to the temperature increases. This was different from the snowmelt-dominated basins in China, such as Tarim River, western China [43] and Yarlung Zangbo River on the Tibetan Plateau [44], where elevated temperature produced higher stream flow because of enhanced snowmelt. However, as a whole, stream flow was more sensitive to precipitation than evaporation in the Poyang Lake Basin [45].…”
Section: Impacts Of Climate Change On Stream Flow Variationsmentioning
confidence: 66%
“…The 114 rivers in the TRB connected with the mainstream reduced throughout history to just 3 rivers in the present day [33]. The mean annual runoff of 3.989 × 10 10 m 3 is exhibited in the TRB, where the water component from ice and snow and precipitation in the mountains accounts for 48.2% [33,34]. The three largest headstreams, Aksu River, Hotan River, and Yarkand River, account for 73.2%, 23.2%, and 3.6% of the total runoff, respectively [35].…”
Section: Study Areamentioning
confidence: 99%
“…Additionally, Advances in Meteorology 3 the annual air temperature in the TRB exhibits intra-annual variations [33]. The barren and sparsely vegetated land plays major role in the land use in the TRB, which accounts for 56.2% [34].…”
Section: Study Areamentioning
confidence: 99%
“…These studies employed methods designed under the hypothesis that the time series of hydroclimatic variables are stationary and therefore can be considered as a linear system (such as moving average or polynomial, linear regression, empirical or spline function fitting) [11]. However, studies also found that hydroclimatic processes are complex and hydroclimatic variables, including runoff, precipitation, temperature and evapotranspiration, often behave nonlinearly and nonstationarily [12,13]. Therefore, traditional (i.e., linear interpretation) methods cannot satisfy for capturing nonlinear, nonstationary response patterns of streamflow to climatic variability.…”
Section: Introductionmentioning
confidence: 99%